The influence of perceived system quality and perceived information quality towards continuance intention of tax e-filing system in Malaysia - Chandra, Punitha; Ibrahim, Amlus (UUM College of Business, 2015)
In the current globalization arena, government of each countries facing challenges and keep on finding the better ways to provide the better government services to the their stakeholders.For that governments in each countries including Malaysia have been spent huge amount of money for the development of electronic government (e-government) and specifically in e-filing system to ease the government services.At this vein, investigation on factors that influences continuance intention is important because ineffective usage of e-government service after initial adoption caused undesirable cost and waste of development of particular e-government service. Most of the prior studies focused more on individuals' adoption intention of e-government services, however, there are limited empirical studies that focused on continuance intention which is about what happens beyond the initial adoption stage in e-government studies and particularly in e-filing context in Malaysia.Thus given the paucity of research on continuance intention, this study attempts to examine the influence of perceived system quality and perceived information quality towards continuance intention of tax e-filing system using a review of literature.